Sports performance: is there evidence that the body clock plays a role? - Reilly, T.; Waterhouse, J. (European Journal of Applied Physiology, 2009)
Athletic performance shows a time-of-day effect, possible causes for which are environmental factors (which can be removed in laboratory studies), the sleep-wake cycle and the internal "body clock". The evidence currently available does not enable the roles of these last two factors to be separated. Even so, results indicate that the body clock probably does play some role in generating rhythms in sports performance, and that to deny this is unduly critical. Protocols to assess the separate roles of the body clock and time awake are then outlined. A serious impediment to experimental work is muscle fatigue, when maximal or sustained muscle exertion is required. Dealing with this problem can involve unacceptably prolonged protocols but alternatives which stress dexterity and eye-hand co-ordination exist, and these are directly relevant to many sports (shooting, for example). The review concludes with suggestions regarding the future value to sports physiology of chronobiological studies.